THE MOSQUE BASED ZAKAT MANAGEMENT: A STUDY OF AMIL ZAKAT EXISTENCE IN BANJARMASIN - Budi Rahmat Hakim; Edi Gunawan Gunawan (IAIN Manado, 2020)
The main problem in this study is the legality of zakat managers' existence and the effectiveness of zakat management at mosques and langar in Banjarmasin as the most significant potential among Banjarmasin people who are known to be religious. The research seeks to reveal the existence and role, and efforts to revitalize the presence and function of amil zakat formed by the ta'mir/ mosque administrators who are the research objects. The research method applied is classified as field research. The research type is qualitative research. Data mining is carried out by interviewing the mosque ta'mir administrators and the committee / amil zakat and BAZNAS Banjarmasin administrators. Also, data collection is carried out by documentation. Based on the study results, it was found that the existence of amil zakat in most mosques in Banjarmasin. According to the zakat law, the form of committees was formed seasonally before Eid al-Fitr and did not formally and permanently establish management as Zakat Collection Units (UPZ). Only a small number of them have officially started the administration of amil zakat to become UPZ. The existence of amil, which is only ad hoc, has not shown the maximum function and role in the direction of zakat, especially in the management of zakat fitrah. Most of the amil/zakat committees formed by mosque administrators are only limited to serving the acceptance and distribution of zakat fitrah. The type of zakat mal is still relatively small. Regarding the optimization of the collection, especially the kind of zakat mal, the amil / mosque zakat committee, which is the subject of this research, has never made any efforts to pick up the ball (zakat mal) to the surrounding muzaki. Socialization or invitations for zakat distribution through amil's mosque are also only carried out in limited media (through mosque loudspeakers or banners).